Um estudo comparativo sobre as técnicas de controle de acesso combinando RFID e biometria - Machado, Suzy Brenda Nascimento (Brasil, 2020)
This work aims to demonstrate and evaluate existing technologies based on the combination of RFID and biometric techniques based on facial recognition and fingerprint, in the form of a comparative study on access control techniques for projects related to the security area, in order to compare and verify which access control technologies can present better security, reliability and adaptability to the environment. Studies and experiments were carried out with RFID technology combined with face recognition and digital printing, to compare which technology has better behavior with RFID. It was possible to verify that the two biometric techniques demonstrate satisfactory results, highlighting the fingerprint recognition as the technique that presented less time and higher percentage of correct answers. The relevance and contribution of this work is given by the approach of combining existing technologies that provide better results in relation to the factors of reliability, integrity and availability, in addition to their contribution to future work in this area.